Pemberdayaan Kader dalam Pemanfaatan Buku KIA untuk Optimalisasi Keteraturan Pemeriksaan Kehamilan - Triyawati, Lilik; Latip, Abdul; Wahyuni, Sri (IKIP PGRI Bojonegoro, 2025)
Regular Antenatal care is very important because it helps reduce complications in pregnancy and childbirth. The aim of this community service is to increase the knowledge and skills of Village Health Cadres regarding the use of KIA books in Sumberagung Village, Dander District, Bojonegoro Regency. This activity was carried out in the form of training regarding the use of the KIA book. The training was carried out for 3 (three) days attended by 30 participants using the lecture method, question and answer, practice in using the KIA book and KIE practice. The result of the activity was that 30 cadres were trained, there was an increase in the lowest, highest and average knowledge scores of the training participants. Most (80%) of the training participants had very good post scores (79-100), the average score of participants' skills in using the KIA book is 83.3% and skills in extension are the majority (80%) have a very good value of extension skills (79-100), the formation of a joint commitment, all cadres (100%) have carried out outreach to the community around where they live on an ongoing basis so that can improve the health status of mothers and children.